ABDULLAH BIN NUH: HIS STRUGGLE ON DA’WAH THROUGH ISLAMIC EDUCATION - Mohammad Noviani Ardi (Kopertais Wilayah X Jawa Tengah, 2017)
AbstractThis study provides Abdullah bin Nuh and his struggle on Da’wah to reveal his contribution in the Da’wah of Islam particularly in Islamic education. In methodology, this paper used in-depth literature review and an analysis to highlight his noble works in order to increase prestige of Islam in Indonesia through education field. This study finds that Abdullah bin Nuh has great contribution in Indonesia, he very concerned in education with continually Islamic teaching and discourses to his students. This concerning were evidenced with the founding of two Islamic centers in Bogor both al-Ghazaly and al-Ihyaa with Islamic programs and discourses for public society and students (santri) as well. Moreover, in the regard to make good intellectual foundation among students of university, he also held several special discourses about Islamic teaching frequently. Therefore, in order to support his da’wah on Islamic education his consistently translated several classical Arabic books particularly al-Ghazaly’s works to Indonesia and Sundanese language to make easier his students understanding. Finally, this paper presents the aspect life of Abdullah bin Nuh which did not covered yet by Indonesian Muslim today and to promote his struggle and contribution in da’wah of Islam in Indonesia.